Fashion-preneur and Social Media: A strategy to Enhance Teens’ Awareness, Trust and Loyalty towards Indonesian Local Fashion Brands - Hapsari, Raditha; Thongkern, Thitiya; Zaini, M. Taufiq (APMBA (Asia Pacific Management and Business Application), 2023)
This current study aims to examine the role of social media marketing, brand awareness, value, and trust in local fashion brand loyalty. This study uses the affective-cognitive theory that stated to create an emotional response, a customer of a brand needs to evaluate the affective and cognitive stimuli provided by the brand. This current study focuses on investigating the effect of social media marketing and brand awareness (cognitive); trust and perceived value (affective) on loyalty. One hundred and fifty respondents from Indonesian local fashion brands have participated in the survey were recruited by using a purposive sampling technique. Structural Equation Modelling (AMOS 20) was used to analyze the data, through two steps: Confirmatory Factor Analysis (CFA) and hypothesis testing. The result of the CFA test confirmed that the indices were all acceptable. The results of the hypothesis testing show that social media marketing positively influenced customers’ perceived value, brand awareness, and brand trust while brand loyalty is influenced by the marketing activity that is done through social media, the degree of customers’ brand awareness, brand trust, and perceived value. Based on the result of this study, to make the customers loyal to the brand in the fashion industry, fashion-preneur must deliver the right social media marketing campaign.